Sleep bruxism in children, from evidence to the clinic. A systematic review - Claudia Restrepo-Serna; Efraim Winocur (Frontiers Media S.A., 2023)
ObjectivesThe present paper aims to systematically review the literature published from 2015 to 2023 on bruxism in children with the aim to compilate the best available evidence.Materials and MethodsA systematic search in the National Library of Medicine's PubMed, Medline (EBSCO), SCOPUS, and Google Scholar databases was performed to identify all studies on humans assessing genetic, biopsychosocial, and sleep factors assessed with any different approach for sleep bruxism (SB) in children and its interventions. The selected articles were assessed independently by the two authors according to a structured reading of the article's format (PICO). The quality of the articles was evaluated using Quality Assessments Tool for Experimental Bruxism Studies (Qu-ATEBS) and the JBI critical appraisal tools.ResultsA total of 16 articles were included for discussion in the review and grouped into questionnaire/parental-report (n = 7), SB assessment through parental report of SB and clinical examination (n = 4), and instrumental assessment (n = 5) studies. The total quality scores evaluated with STROBE and Qu-ATEBS were high for all included papers. However, in general, there was no control of bias strategies and there was no control group in the intervention studies.ConclusionsInvestigations based on self-report, clinical, and instrumental bruxism assessment showed a positive association with genetics, quality of life aspects (school and emotional functions and overuse of screen-time), mother anxiety and family conformation, diet, alteration in sleep behaviors and architecture, and sleep breathing disorders. Additionally, the literature presents options to increase airway patency and, thus, reduce the occurrence of SB. Tooth wear was not found to be a major sign of SB in children. However, methods of SB assessment are heterogeneous and hamper a reliable comparison of the results.